Powieść reportażowa czy dziennikarska? Uwagi o międzywojennej twórczości prozatorskiej Jalu Kurka - Adamczewska, Izabella (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The paper focuses on genealogical aspects of three interwar novels by Jalu Kurek – Andrzej Panik, Grypa szaleje w Naprawie, Woda wyżej) – which have often been described by critics as “reportage novels”. The author examines the past critical reception of the novels and the intentio auctioris. The main goal of the article is to suggest a more capacious genealogical term: the journalistic novel.